“Instagramable” : Simulation, Simulacra And Hyperreality on Instagram Post - Maria Febiana Christanti; Puri Bestari Mardani; Intan Putri Cahyani; Windhiadi Yoga Sembada (International Journal of Social Service and Research, 2021)
The relationship between social media and individuals is complex. Like how humans flock to form an 'instagramable' culture on Instagram. The author examines this complexity using the lens of Jean Baudrillard in writings on simulation and simulacra. Baudrillard's main argument is that nothing in our culture is "real" in any sense. "Simulacrum", consider as something that is real, which is a depiction or copy of something that does not exist. Instagram is a social media that makes humans addicted to signs and symbols through "instagramable" photos and videos. This research provides knowledge about the potential reality of reality from polished photos or videos uploaded to Instagram. This study uses qualitative research with a phenomenological approach and uses dramaturgy theory (front and backstage) to reveal the reality and falsehood of "instagramable" images. This study analyzes using four stages, namely reflection of the deep reality, covering and denaturing the deep reality, covering the absence of deep reality, having nothing to do with any reality; it is its pure simulacrum. The result of this research is that simulacra are more than a process. Each stage carried out by Instagram users characterizes a level of simulation. Research gives insight to us that "instagramable" simulations are imaginations that are not entirely true or not true